First report of Acanthochaetetes (Porifera: Demospongiae) from the Cretaceous Khalsi Formation, Ladakh Himalaya, India. (November 2021) - Barman, Prasenjit; Sánchez-Beristain, Francisco; Mishra, Shruti Ranjan; Ibrahim, Mohd; Swami, Narendra Kumar; Bamniya, Mukesh; Singh, Shailendra
Abstract: The Cretaceous chaetetid sponge Acanthochaetetes huauclillensis Sánchez-Beristain and García-Barrera is reported for the first time from the Aptian–Cenomanian Khalsi Formation, Ladakh Himalaya, India. Its low- to high-domical growth form could suggest an adaptation to either an environment with constant sedimentation rates, or to an irregular substrate. However, these growth forms also may indicate an absence of important environmental/sedimentological changes during the lifespan of the sponges. In addition, the growth form of this species suggests a calm, non-turbulent, reef-like microenvironment. Along with the other faunal assemblages, such as the rudists, corals, and the gastropod Nerinea, A . huauclillensis indicates a tropical to subtropical shallow marine carbonate platform setting. This new finding extends its stratigraphic range from the upper Hauterivian to the Aptian–Cenomanian interval in the eastern Tethyan realm.